2022
DOI: 10.3390/vetsci9060269
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterisation of Multiresistant Bacterial Strains Isolated in Pigs from the Island of Tenerife

Abstract: Background: Antibiotic-resistant bacteria can circulate among human and animal populations through direct contact with animals, as well as via food and the environment. The purpose of this study was to examine the prevalence and characterisation of multiresistant bacteria in pig samples. Methods: 224 samples of pig livestock were taken at the slaughterhouse on the island of Tenerife. A nasal and a rectal sample were collected from each pig. The presence of methicillin-resistant Staphylococcus aureus (MRSA), me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Although the data indicated that most bacteria are still sensitive to individual antimicrobials, the multi-resistance characteristics of foodborne pathogens have been referred to as an important issue [ 173 , 174 ].…”
Section: Surveillance Of Antibiotic Resistance In the Slaughterhousementioning
confidence: 99%
“…Although the data indicated that most bacteria are still sensitive to individual antimicrobials, the multi-resistance characteristics of foodborne pathogens have been referred to as an important issue [ 173 , 174 ].…”
Section: Surveillance Of Antibiotic Resistance In the Slaughterhousementioning
confidence: 99%
“…Several studies have reported that people that work or live in pig farms, including farmers and their families, abattoir staff, and veterinarians, are at high risk of contracting LA-MRSA from pigs [4,13,33,34,43,78,[108][109][110][111][112]. In Belgium, 37.8% of people working or living in 25 out of the 49 pig farms investigated were infected with LA-MRSA CC398 [108].…”
Section: Pigs-human Transmissionmentioning
confidence: 99%
“…To date, LA-MRSA has rarely been reported outside communities exposed to LA-MRSA-positive pigs [35,43,98,[119][120][121]. Several studies analyzed the human-to-human transmission of LA-MRSA CC398 in hospitals.…”
Section: Transmission Between Humansmentioning
confidence: 99%
See 2 more Smart Citations